Study on the Rubber Powder Composite for Rubber Car Mats Application - Mohd Sangit, Muhammad Syahrul Azhar; Ismail, Norhasikin (Progress in Engineering Application and Technology, 2025)
This research focuses on developing rubber car mats using waste rubber powder as a sustainable alternative to traditional raw rubber, motivated by the rising cost of raw rubber due to reduced natural rubber production by the Organization of the Rubber Exporting Countries (OPEC). The research aims to provide an environmentally friendly and cost-effective solution for automotive applications while maintaining mechanical performance. Rubber composites were prepared by mixing waste rubber powder with epoxy resin and hardener in varying weight ratios (20%, 30%, 40%, and 50%). 120g of each sample was fabricated and tested according to ASTM standards: tensile strength (ASTM D638 Type 4), bending strength (ASTM D790), and impact resistance (ASTM D256). The mechanical testing revealed that 20% exhibited the highest tensile strength (15.7 MPa) and bending strength (62.58 MPa), while 50% showed the highest impact strength (6.66 MPa) with energy absorption of 1.34%. However, composite analysis determined that percentages did not provide the best mechanical properties for car mat applications. The result analysis is not in the range of actual impact strength for a rubber car mat. Generally, not all percentages of rubber car mats are as elastic as a common rubber car mat. at the market. This study can be used for other suitable applications such as car bumpers, car spoilers and car skirting